Melanoma: Risk factors, early detection, and treatment strategies-An updated review - Albogamy, Sahar Adi; Alnemer, ‏Maram Jaafar; Aljawad, ‏Hussain Mahdi; Alanazi, Alaa Saud K; Alharbi, ‏Abdulalah Thabet; Al-Harbi, Mohammed Saad Ali; Algfari, Sultan Mohammed (International journal of health sciences, 2023)
Background: Melanoma is a significant and aggressive form of skin cancer originating from melanocytes. The rising incidence of melanoma, particularly among younger populations, underscores the need for increased awareness and early detection. Aim: This review aims to provide a comprehensive overview of the risk factors, early detection methods, and treatment strategies for melanoma, emphasizing recent advancements in the field. Methods: The review synthesizes current literature regarding melanoma’s epidemiology, etiology, clinical presentation, diagnostic techniques, and therapeutic approaches. Emphasis is placed on advancements in immunotherapy, targeted therapies, and emerging nanotechnology-based strategies. Results: The global incidence of melanoma is increasing, with environmental factors such as UV radiation being the primary modifiable risk factor. Innovative treatment options, including immune checkpoint inhibitors and small-molecule kinase inhibitors, have shown promising results, although challenges such as drug resistance and adverse side effects remain. Recent clinical trials indicate that combination therapies may enhance treatment efficacy. Nanotechnology has emerged as a valuable tool for improving drug delivery and targeting tumor sites effectively. Conclusion: Melanoma poses a serious public health challenge due to its aggressive nature and rising incidence. Early detection through routine skin examinations and awareness of risk factors is crucial for improving outcomes.